Cross talk between adenosine A2A receptors and the Trk receptores for brain-derived neurotrophic factor (BDNF) at the rat hippocampus - Diógenes, Maria José (2010)
Tese de doutoramento, Ciências Biomédicas (Neurociências Básicas), Universidade de Lisboa, Faculdade de Medicina, 2009